Optimal. Leaf size=20 \[ e^{-2 x} \left (x+x^2+\frac {x}{3 \log (4)}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.08, antiderivative size = 31, normalized size of antiderivative = 1.55, number of steps used = 12, number of rules used = 4, integrand size = 28, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.143, Rules used = {12, 2196, 2194, 2176} \begin {gather*} e^{-2 x} x^2+e^{-2 x} x+\frac {e^{-2 x} x}{3 \log (4)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 2176
Rule 2194
Rule 2196
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int e^{-2 x} \left (1-2 x+\left (3-6 x^2\right ) \log (4)\right ) \, dx}{3 \log (4)}\\ &=\frac {\int \left (e^{-2 x}-2 e^{-2 x} x-3 e^{-2 x} \left (-1+2 x^2\right ) \log (4)\right ) \, dx}{3 \log (4)}\\ &=\frac {\int e^{-2 x} \, dx}{3 \log (4)}-\frac {2 \int e^{-2 x} x \, dx}{3 \log (4)}-\int e^{-2 x} \left (-1+2 x^2\right ) \, dx\\ &=-\frac {e^{-2 x}}{6 \log (4)}+\frac {e^{-2 x} x}{3 \log (4)}-\frac {\int e^{-2 x} \, dx}{3 \log (4)}-\int \left (-e^{-2 x}+2 e^{-2 x} x^2\right ) \, dx\\ &=\frac {e^{-2 x} x}{3 \log (4)}-2 \int e^{-2 x} x^2 \, dx+\int e^{-2 x} \, dx\\ &=-\frac {1}{2} e^{-2 x}+e^{-2 x} x^2+\frac {e^{-2 x} x}{3 \log (4)}-2 \int e^{-2 x} x \, dx\\ &=-\frac {1}{2} e^{-2 x}+e^{-2 x} x+e^{-2 x} x^2+\frac {e^{-2 x} x}{3 \log (4)}-\int e^{-2 x} \, dx\\ &=e^{-2 x} x+e^{-2 x} x^2+\frac {e^{-2 x} x}{3 \log (4)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.04, size = 19, normalized size = 0.95 \begin {gather*} \frac {e^{-2 x} x (1+\log (64)+x \log (64))}{\log (64)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.65, size = 23, normalized size = 1.15 \begin {gather*} e^{\left (-2 \, x + \log \left (\frac {6 \, {\left (x^{2} + x\right )} \log \relax (2) + x}{6 \, \log \relax (2)}\right )\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.13, size = 33, normalized size = 1.65 \begin {gather*} \frac {6 \, x^{2} e^{\left (-2 \, x\right )} \log \relax (2) + 6 \, x e^{\left (-2 \, x\right )} \log \relax (2) + x e^{\left (-2 \, x\right )}}{6 \, \log \relax (2)} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.09, size = 25, normalized size = 1.25
method | result | size |
gosper | \({\mathrm e}^{\ln \left (\frac {x \left (6 x \ln \relax (2)+6 \ln \relax (2)+1\right )}{6 \ln \relax (2)}\right )-2 x}\) | \(25\) |
risch | \(\frac {\left (2 \left (3 x^{2}+3 x \right ) \ln \relax (2)+x \right ) {\mathrm e}^{-2 x}}{6 \ln \relax (2)}\) | \(26\) |
norman | \({\mathrm e}^{\ln \left (\frac {2 \left (3 x^{2}+3 x \right ) \ln \relax (2)+x}{6 \ln \relax (2)}\right )-2 x}\) | \(28\) |
default | \(\frac {{\mathrm e}^{-2 x} x +6 \,{\mathrm e}^{-2 x} \ln \relax (2) x^{2}+6 \,{\mathrm e}^{-2 x} \ln \relax (2) x}{6 \ln \relax (2)}\) | \(34\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [B] time = 0.35, size = 49, normalized size = 2.45 \begin {gather*} \frac {6 \, {\left (2 \, x^{2} + 2 \, x + 1\right )} e^{\left (-2 \, x\right )} \log \relax (2) + {\left (2 \, x + 1\right )} e^{\left (-2 \, x\right )} - 6 \, e^{\left (-2 \, x\right )} \log \relax (2) - e^{\left (-2 \, x\right )}}{12 \, \log \relax (2)} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 8.95, size = 78, normalized size = 3.90 \begin {gather*} \frac {{\mathrm {e}}^{-2\,x}\,\left (x-3\,\ln \relax (2)+\ln \relax (8)+72\,x^2\,{\ln \relax (2)}^2+36\,x^3\,{\ln \relax (2)}^2+3\,x\,\ln \relax (2)+x\,\ln \left (512\right )+36\,x\,{\ln \relax (2)}^2+6\,x^2\,\ln \relax (2)+x^2\,\ln \left (64\right )\right )}{6\,\ln \relax (2)\,\left (6\,\ln \relax (2)+6\,x\,\ln \relax (2)+1\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.16, size = 26, normalized size = 1.30 \begin {gather*} \frac {\left (6 x^{2} \log {\relax (2 )} + x + 6 x \log {\relax (2 )}\right ) e^{- 2 x}}{6 \log {\relax (2 )}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________